Numerical Study of Hydrogen Combustion on Micro Combustor with Exhaust Gas Recirculation Jacket for Enhancement of Emissive Power - Kaewpradap, Amornrat; Jugjai, Sumrerng (Recent Science and Technology, 2024)
This research is to study the numerical model of hydrogen combustion in a micro combustor to enhance the energy converted to electricity by analyzing wall temperature and emissive power. This research focuses on the affected parameters of micro combustor geometry (rectangle, cylinder, hexagon), exhaust gas recirculation (EGR) at a hydrogen mass flow rate of 1.8551x10-5 kg/s, and an equivalence ratio of 1.0. As the result, wall temperatures ranging from 18.8 to 19.7 oC and emissive power between 12.2 and 12.4% were observed from cylindrical and hexagonal micro combustor, which were higher than those of rectangular micro combustor. Moreover, the installation of hexagonal EGR and cylindrical EGR with micro combustor could enhance emissive power by 1.6 and 2.0 watt, respectively. This study indicates that the design of a cylindrical micro combustor with cylindrical EGR, covered with porous media, could achieve the highest emissive power of 12.26 watts, which is 33.7% higher than that of the referenced model.